Constructivism in the Digital Age: How Celebrity Influence and Social Media Richness Impact Youth's Perceived Absorption Capacity and Societal Polarization - Binesh Sarwar; Salman Zulfiqar; Chunhui Huo; Khurram Ejaz Chandia; Saira Aziz (Sustainable Futures)
The rapid spread of social media has transformed individual discourse and societal behavior, particularly among youth. This study explores how patronized celebrity influence on social media impacts the perceived absorption capacity of youth in Pakistan, contributing to societal polarization. Grounded in constructivism theory, the research model proposes that social media richness positively affects youths' absorption capacity, strengthened by patronized celebrity endorsements. Data collected from 573 young social media users using a time-lag method reveal that social media richness significantly enhances perceived absorption capacity, with celebrity influence acting as a moderator. Moreover, perceived absorption capacity partially mediates the link between social media richness and societal polarization. These findings underline the need for policymakers and educators to implement strategies and digital literacy programs to empower youth as critical social media consumers. The implications of study underscore the necessity for targeted policy interventions and digital literacy initiatives to foster critical social media engagement among youth.